Factors associated with herpes simplex virus type 2 incidence in a cohort of human immunodeficiency virus type 1-seronegative Kenyan men and women reporting high-risk sexual behavior. - Okuku, H; Sanders, E; Nyiro, J; Ngetsa, C; Ohuma, E; McClelland, R; Price, M; Graham, S (2011)
BACKGROUND: Herpes simplex virus type 2 (HSV-2) is an important cause of genital ulcers and can increase the risk for human immunodeficiency virus type 1 (HIV-1) transmission. Our objective was to determine the incidence and correlates of HSV-2 infection in HIV-1-seronegative Kenyan men reporting high-risk sexual behavior, compared with high-risk HIV-1-seronegative women in the same community. METHODS: Cohort participants were screened for prevalent HIV-1 infection. HIV-1-uninfected participants had regularly scheduled follow-up visits, with HIV counseling and testing and collection of demographic and behavioral data. Archived blood samples were tested for HSV-2. RESULTS: HSV-2 prevalence was 22.0% in men and 50.8% in women (P < 0.001). HSV-2 incidence in men was 9.0 per 100 person-years, and was associated with incident HIV-1 infection (adjusted incidence rate ratio [aIRR], 3.9; 95% confidence interval [CI], 1.3-12.4). Use of soap for genital washing was protective (aIRR, 0.3; 95% CI, 0.1-0.8). Receptive anal intercourse had a borderline association with HSV-2 acquisition in men (aIRR, 2.0; 95% CI, 1.0-4.1; P = 0.057), and weakened the association with incident HIV-1. Among women, HSV-2 incidence was 22.1 per 100 person-years (P < 0.001 compared with incidence in men), and was associated with incident HIV-1 infection (aIRR, 8.9; 95% CI, 3.6-21.8) and vaginal washing with soap (aIRR, 1.9; 95% CI, 1.0-3.4). CONCLUSIONS: HSV-2 incidence in these men and women is among the highest reported, and is associated with HIV-1 acquisition. Although vaginal washing with soap may increase HSV-2 risk in women, genital hygiene may be protective in men.